Pengaruh Pengalaman Kerja, Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Guru (Studi Kasus pada Guru SMA Negeri 01 Batu) - Indahsari, Sesarini Rahma; Nurhajati, Nurhajati; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to identify and analyze the influence of work experience, work discipline and job satisfaction on teacher performance at SMA Negeri 01 Batu. The method used is quantitative research with a descriptive approach. The population in this study includes all teachers at SMA Negeri 01 Batu, totaling 68 people, with a sampling technique using the saturated sample method, so that all teachers are used as respondents. The data collected are primary data through questionnaires. Data analysis was carried out using various statistical tests, including instrument validity and reliability tests, normality tests, and classical assumption tests including multicollinearity and heteroscedasticity tests. In addition, this study uses multiple linear regression analysis and hypothesis testing, consisting of simultaneous tests, partial tests, and coefficients of determination. The findings of this study reveal that teacher performance is significantly influenced by work experience, work discipline, and job satisfaction. Collectively, these factors play a crucial role in shaping performance. When examined individually, work experience has a positive and significant impact on teacher performance. Likewise, work discipline positively and significantly affects teacher performance, while job satisfaction also exerts a significant positive influence. Keywords: Work experience, work discipline, job satisfaction and teacher performance